Implementasi Program Raskin Dalam Upaya Meningkatkan Kesejahteraan Masyarakat - ', Sujianto; ', Ernawati; As’ari, Hasim; ', Mayarni (Universitas Riau, 2012)
The purpose of thisstudy is to analyze and explain the mechanism of the implementation of the Program Raskin (Ricefor the Poor) in an effort to improve the welfare of the poor in New Seacoast village of Kerincidistrict Pelalawan. The research relies on interviews with informants between researchersdeliberately researchers determine in accordance with the needs of the required information. Laterobservations for viewing and analyzing events in the field. The results show the distribution ofRaskin in New Seacoast Village goes poorly, it is because at the time the distribution is still foundsome problems that a lot can hinder the process of distribution of Raskin himself.